The Chameleon Workforce: Assembeling and Negotiating the Content of a Workforce - Mikkel Mouritz Marfelt (Copenhagen Business School (CBS), 2016)
Due to advancements in technology and the expansion of companies onto a global level, organizations have become increasingly aware of the need to understand and manage diverse workforces; that is, the need to understand and manage differences among employees across borders (such as geographical, cultural, professional, etc.). This PhD dissertation studies this phenomenon, `a diverse workforce', in a large Scandinavian pharmaceutical company. The dissertation follows the Diverse and Global Workforce (DGW) project, a `headquarter centric' and strategic corporate initiative to address the rapid global expansion of the company workforce. In academia, the phenomenon has been studied widely for the last three decades under the overarching research field `workforce diversity'. While workforce diversity research has contributed to a better understanding of the concept of diversity in work-related situations, the role of `workforce' in this equation is often assumed, reducing the problematic of workforce diversity to a need to understand the concept of `diversity in the workforce'. This perception is not without its problems and has led to a focus on the concept of diversity at the expense of understanding the role of the workforce as something other than a simple container of `people engaged in or available for work'. And so, even though the `workforce' was foundational to forming workforce diversity research and its related fields (such as diversity management, diversity at work, diversity in the workplace, etc.), discussions about the role of the workforce have become a peripheral debate, while discussions on the role of diversity have become central.
hdl:10398/9285
Keywords: 650